CRYSTAL-CHEMICAL CONTROLS ON THE PARTITIONING OF SR AND BA BETWEEN PLAGIOCLASE FELDSPAR, SILICATE MELTS, AND HYDROTHERMAL SOLUTIONS - Blundy J.D.; Wood B.J. (My University, 1991)
The isothermal (750°C) experiments of Lagache and Dujon (1987) reveal that the partitioning of Sr between plagioclase feldspar and hydrothermal solutions is a funtion of the anorthite (An) content of the plagioclase, indicating that crystal chemistry may exert a powerful influence on trace element partitioning. In order to compare these results with those on trace element partitioning between plagioclase and silicate melts we have compiled from the literature a large dataset of experimental and volcanic distribution coefficients (D's) for Sr (and Ba). These data, which span a compositional range from lunar basalt to high silica rhyolite and a temperature range of over 650°C, show a relationship between DSr (and DBa) and mole fraction An (XAn) which is similar to that exhibited by the hydrothermal results obtained at constant temperature. Plots of In DSr and In DBa versus XAn are linear with negative slope, indicating that both elements are more compatible in albite than anorthite. In terms of molar distribution coefficients ( ) the hydrothermal and silicate melt data display an identical linear relationship between RT In (where T is the absolute temperature in K and R is the gas constant, 8.314 JK−1 mol−1) and XAn. We conclude therefore that crystal chemistry provides the dominant control on partitioning of Sr and Ba into plagioclase and that the effects of temperature, pressure, and fluid composition are minor. Apparent relationships between DSr (and DBa) and the reciprocal temperature (1/T) are artefacts of the linear relationships between XAn and 1/T in the experimental studies.